rs3761548 (C/A) and rs5902434 (del/ATT) polymorphisms of Foxp3 gene in Iranian patients with migraine - Fardin Faraji; Ghasem Mosayebi; Maryam Bahrami; Mana Shojapour (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Background Migraine is a neurovascular disorder; several studies have demonstrated the immune system plays a key role in migraine pathogenesis. The aim of this study was to investigate the association between FOXP3 gene polymorphism and susceptibility to migraine. Methods In a case–control study, 55 whole blood samples of patients with migraine and 80 healthy samples were collected. After DNA extraction, genotyping of the rs5902434 (del/ATT) and rs3761548 (C/A) FOXP3 was performed using sequence-specific primers method (PCR-SSP). Results The results of this study showed that there were statistically significant differences between patient and control group in genotype frequencies of rs3761548. In addition, the frequency of heterozygous genotype AC at rs3761548 in patients was found to be significantly higher than controls. We also found no significant differences between cases and controls were found in the allelic and genotype distribution of the rs5902434 (del/ATT) polymorphism. None of the rs5902434 (del/ATT) genotypes showed any significant association with the migraine. Conclusions According to finding of our study, polymorphism rs3761548 in FOXP3 gene were associated with susceptibility to migraine. Further studies with larger sample sizes and different populations in other parts of the world are needed to investigate relationship between this polymorphism on migraine susceptibility.